2020
DOI: 10.1177/1535370220920540
|View full text |Cite
|
Sign up to set email alerts
|

Novel 2019 coronavirus: Genome structure, clinical trials, and outstanding questions

Abstract: Novel 2019 coronavirus has created havoc across the globe since its emergence in December 2019 in Wuhan, China, and fast spreading potential. While we were able to identify the causative agent within a few days of the disease outbreak, several questions still remain unanswered. In this review, we discuss the extent of virus spread, current statistics, SARS-CoV-2 genome organization, comparison between the novel coronavirus and causative agents involved in previous outbreaks, ongoing clinical trials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 32 publications
0
29
0
1
Order By: Relevance
“…A new RNA betacoronavirus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the illness COVID-19 [ 1 3 ] that has resulted in, and continues to cause severe global morbidity and mortality. COVID-19 was classified as a global pandemic by the World Health Organization (WHO) on March 11, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…A new RNA betacoronavirus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the illness COVID-19 [ 1 3 ] that has resulted in, and continues to cause severe global morbidity and mortality. COVID-19 was classified as a global pandemic by the World Health Organization (WHO) on March 11, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the United States, Remdesivir, previously used to treat Ebola, is being tested 9 in Trials NCT04292899, NCT04280705, and NCT04292730, which are still in the recruiting phase. 10 Moreover, 158 11 clinical trials are investigating the effects of hydroxychloroquine, an anti-malarial drug, as in-vitro studies have shown its efficacy. 12 The results of these trials are highly anticipated.…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 is caused by a novel beta-coronavirus family member called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). 2,3 In December 2019 (and potentially earlier, though unrecognized), SARS-CoV-2 emerged as a peculiar pneumonia-causing virus in Hubei province, China, most likely as a result of natural selection in animal hosts (bats, pangolins) prior to zoonotic transfer. There are now seven members of this viral family that are known to infect humans with three having the potential to cause a severe respiratory disease.…”
Section: Introductionmentioning
confidence: 99%